1999
DOI: 10.1046/j.1365-2141.1999.01730.x
|View full text |Cite
|
Sign up to set email alerts
|

NG2 expression in MLL rearranged acute myeloid leukaemia is restricted to monoblastic cases

Abstract: Summary. Expression of NG2 has been reported in the majority of paediatric acute leukaemia (AL) cases with MLL rearrangement. We demonstrated 7.1 positivity in 2/3 paediatric and 4/11 adult MLL rearranged acute myeloid leukaemia (AML) but in 0/28 adult AML without MLL rearrangement, thus extending the 100% speci®city to adult cases. Positivity correlated with stage of maturation arrest since it was found in 0/6 immature AML but in 6/8 monoblastic cases. These data demonstrate that, if NG2 expression in AL is t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 8 publications
0
21
0
1
Order By: Relevance
“…[54][55][56][57][58] Moreover, commonly seen in the clinic are leukemic patients harboring MLL rearrangements but lacking NG2 expression (Table 1). 55,57,59 Conversely, there are a proportion of cases in which expression of NG2 is clearly detected in the absence of MLL rearrangements. 56,57 More recently, it has been suggested that 7.1 expression could be specifically associated with only two specific subtypes of leukemia harboring either the translocations t(4;11)(q21;q23) or t(9;11)(p13;q23), which encode for the leukemic fusion genes MLL-AF4 and MLL-AF9, respectively, but not for other MLL rearrangements.…”
Section: Environmental Exposures and Delayed Infection Early In Life mentioning
confidence: 99%
See 1 more Smart Citation
“…[54][55][56][57][58] Moreover, commonly seen in the clinic are leukemic patients harboring MLL rearrangements but lacking NG2 expression (Table 1). 55,57,59 Conversely, there are a proportion of cases in which expression of NG2 is clearly detected in the absence of MLL rearrangements. 56,57 More recently, it has been suggested that 7.1 expression could be specifically associated with only two specific subtypes of leukemia harboring either the translocations t(4;11)(q21;q23) or t(9;11)(p13;q23), which encode for the leukemic fusion genes MLL-AF4 and MLL-AF9, respectively, but not for other MLL rearrangements.…”
Section: Environmental Exposures and Delayed Infection Early In Life mentioning
confidence: 99%
“…[73][74][75][76] The presence of MSCs harboring these leukemic fusion genes would explain, at least in part, the higher sensibility of the molecular techniques such as quantitative reverse transcriptase PCR over flow cytometry methods for the detection of minimal residual disease because by flow cytometry we just analyze hematopoietic cells. 77 The detection of the BCR/ABL oncogene and lymphoma-specific genetic aberrations in endothelial cells from chronic myelogenous leukemia and B-cell lymphoma patients suggests that endothelial cells may be part of the neoplastic clone [78][79][80] and that hemangioblasts rather than HSCs appear to be target cells for the first oncogenic hit, which could occur during the first Hilden et al 55 Infant AML 45 F Mauvieux et al 59 Pediatric AML 34 F Adult AML 64 F Wuchter et al 57 Childhood Cellular origin and etiology of the infant pro-B ALL C Bueno et al steps of ESC differentiation and/or in hemangioblasts persisting in adults. 81 The cellular organization and relationships among precursors that initiate embryonic angiogenesis and hematopoiesis in humans have been characterized.…”
Section: Environmental Exposures and Delayed Infection Early In Life mentioning
confidence: 99%
“…The specificity approaches 100% in ALL and in childhood AML, sensitivity ranges between 50 and 80% in AML and exceeds 80% in ALL. [5][6][7][8]76 Adult NG2 pos AML cases without MLL rearrangement have been described in one study, indicating lower specificity in adult AML 7 (Figures 1 and 2). Physiologically, NG2 homologue is expressed primarily in glial, muscle and cartilage progenitor cells but not in normal hematopoietic cells.…”
Section: Ng2 Homologue: a Cartilage Trait Pointing To Mll Rearrangemementioning
confidence: 99%
“…Positivity for a specific intracytoplasmic antigen was assumed, if the antigen was expressed in at least 10% of the leukemic cells ('10-cut-off-level'). 19 Reactivity of monoclonal antibody (moab) 7.1, which was previously described to be a highly sensitive and specific marker for leukemic cells with MLL rearrangements (MLL-ra) 20,21 was analyzed by indirect immunofluorescence using moab 7.1 (IgG1; Beckman Coulter, Marseille, France) as mentioned before. 9 In selected experiments we also used the phycoerythrin-conjugated moab 7.1 (Beckman Coulter).…”
Section: Immunophenotypical Analysismentioning
confidence: 99%